Finite element simulation of dislocation field movement - Dłużewski, Paweł; Antuúnez, Horacio (Computer Assisted Methods in Engineering and Science, 1995)
The problem of dislocation motion in monocrystals is faced in the framework of the continuum theory of dislocations. The presented approach is based on the defects balance law. A constitutive model is formulated which relates the driving forces with the dislocation velocity. The model makes use of the relations between the plastic deformation tensor and the tensor of dislocation density. Given a crystal under certain boundary and initial conditions, the evolution of both dislocation field and elastic-plastic deformations is obtained by solving the coupled system of equations resulting from the equilibrium equation and the dislocation balance for each time step. The set of equations is discretized by the finite element method. As an example the movement of an edge dislocation field inducing shear band deformation in a monocrystal is considered.